Geotechnical and geological studies of NWCT tunnel in Iran focusing on the stabilization analysis and design of support: a case study - Ghiasi, Vahed; Omar, Husaini; Rostami, Jamal; Md Yusoff, Zainuddin; Ghiasi, Samad; Kim Huat, Bujang; Muniandy, Ratnasamy (Academic Journals, 2011)
In this paper, a detailed geomechanical investigation of rock masses of North Water Convey Tunnel (NWCT) and its stability analysis has been carried out. The NWCT is located in the north of Iran and is to be constructed in-order to convey water for agriculture purposes. The main instability in the tunnel is joints and faults. The rocks mass encountered in the tunnel route are made of argillaceous, sandstone and shale. The tunnel has been divided into two parts, lot1 and lot2 having a length of 14 km and 26 km respectively. It is proposed to be constructed by telescopic shield method using a tunnel boring machine (TBM). In this study, the most suitable methods are utilized for the stability analysis and design of support of the tunnel. For the empirical investigation, the rock mass were classified based on RMR, Q, RSR, GSI and Rmi systems. The geomechanical properties of the rock mass were determined from the laboratory and field investigations. The results obtained from the analysis show that the tunnel is highly unstable due to the presence of a fault and hence strong supports are need in these regions. The support system used is concrete lining, as the tunnel in used for water conveyance. The tunnel alignment in lot1 is divided into 12 lithology types as; LI-SH1, LI-SH2, LI-SH3, LI-SH4, LI1, LI2, LI3, LI4, LI5, SI, CZ and FZ regions. Similarly, the tunnel alignment in lot2 is divided into 21 lithology types as; SH-ML1, SH-ML2, SH-ML3, MLI-SH1, ML-SH2, ML-SH3, ML-SH4, ML-SH5, SH-LS1, SH-LS2, SH-LS3, SH-LS4, LI2, LI3, LI4, LI5, LI6, LI-MA, LI-SH, CZ, FZ regions. A stability analysis is a necessity as during the tunneling instabilities, such as the presence of a shear zones, may cause an obstruction and delaying of TBM progressing rate.